1973
DOI: 10.1017/s0003356100030294
|View full text |Cite
|
Sign up to set email alerts
|

The response of lactating sows and their litters to different dietary energy allowances. 1. Milk yield and composition, reproductive performance of sows and growth rate of litters

Abstract: SUMMARYTwenty-four gilts were used at each of two centres in an experiment designed to examine the effects of dietary energy intake during lactation on yield and composition of sows' milk and the growth of their litters. Gestation feed intake was standardized at 2 kg per day supplying 6·28 Meal digestible energy (DE) and 280 g crude protein. The energy levels fed during lactation ranged from 12·2 to 18·25 Meal DE per day for gilts, 12·9 to 19·6 Meal DE per day for second parity and from 13·2 to 20·25 Meal DE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 10 publications
6
19
0
Order By: Relevance
“…These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 91%
“…Studies by Elsley et al (1968), O'Grady et al (1973), Adam and Shearer (1975) disagree; however, the pigs in the previous studies received creep feed that may have masked differences in pig weaning weights. Reese et al (1982) reported that the effect of energy intake during lactation on pig weaning weight was variable.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations